Measuring health literacy among low literate people: an exploratory feasibility study with the HLS-EU questionnaire - Hannelore Storms; Neree Claes; Bert Aertgeerts; Stephan Van den Broucke (BMC, 2017)
Abstract Background Health literacy (HL) is defined as necessary competencies to make well-informed decisions. As patients' decision making is a key element of patient-centered health care, insight in patients' HL might help healthcare professionals to organize their care accordingly. This is particularly true for people in a vulnerable situation, potentially with limited HL, who are, for instance, at greater risk of having limited access to care [1, 2]. As HL correlates with education, instruments should allow inclusion of low literate people. To that end, the relatively new instrument, HLS-EU-Q47, was subjected to a comprehensibility test, its shorter version, HLS-EU-Q16, was not. Therefore, the goal of this study was to examine feasibility of HLS-EU-Q16 (in Dutch) for use in a population of people with low literacy. Methods Purposive sampling of adults with low (yearly) income (< €16,965.47) and limited education (maximum high school), with Dutch language proficiency. Exclusion criteria were: psychiatric, neurodegenerative diseases or impairments. To determine suitability (length, comprehension and layout) participants were randomly distributed either HLS-EU-Q16 or a modified version and were interviewed directly afterwards by one researcher. To determine feasibility a qualitative approach was chosen: cognitive interviews were carried out using the verbal probing technique. Results Thirteen participants completed HLS-EU-Q16 (n = 7) or the modified version (n = 6). Questions about 'disease prevention' or 'appraisal' of information are frequently reported to be incomprehensible. Difficulties are attributed to vocabulary, sentence structure and the decision process (abstraction, distinguishing 'appraising' from 'applying' information, indecisive on the appropriate response). Conclusions HLS-EU-Q16 is a suitable instrument to determine HL in people with limited literacy. However, to facilitate the use and interpretation, some questions would benefit from minor adjustments: by simplifying wording or providing explanatory, contextual information.